Circulatory cathepsin K as biomarkers in older adults with sarcopenia: a case-control study - Liu, Huaqing; Liu, Hongdou; Xing, Yan; Wang, Gengze; Wang, Jialin; Fan, Ye; Zhang, Peiwen; Wang, Shangxin; Zhang, Hu (Frontiers in Medicine, 2025)
BackgroundThis study explores the relationship between circulating cathepsin K (CatK) and cathepsin D (CatD) levels and sarcopenia in older adults.MethodsThis case-control study included 343 participants aged more than 65 from Nanyang Central Hospital. Sarcopenia was diagnosed using AWGS criteria, requiring low handgrip strength (HGS) and reduced appendicular skeletal muscle mass (ASM). Fasting blood samples were collected to measure CatD and CatK levels via ELISA. The study compared these levels between groups and evaluated their diagnostic value using ROC curve analysis.ResultsSerum CatK levels were significantly higher in participants with low HGS, low ASM, and sarcopenia (all p < 0.05). CatK negatively correlated with HGS (β = −0.899, p = 0.016) and showed diagnostic value with an AUROC of 0.704 for sarcopenia. CatD levels showed no significant differences or correlations. The optimal CatK cutoff for sarcopenia was 5.53 ng/mL, with high CatK associated with increased odds of low HGS (OR = 1.895, p = 0.014) and sarcopenia (OR = 3.926, p < 0.001).ConclusionCirculating CatK is a promising biomarker for sarcopenia, offering potential for early diagnosis and therapeutic targeting.